A new real-time PCR method for rapid and specific detection of Ling (Molva molva) - Taboada, Lucía; Sánchez, Ana Cristina; González Sotelo, Carmen (Food Chemistry, 2017)
7 páginas, 3 figuras, 3 tablas Seafood fraud – often involving substitution of one species by another – has attracted much attention as it is prevalent worldwide. Whilst DNA analysis has helped to combat this type of fraud some of the methods currently in use are time-consuming and require sophisticated equipment or highly-trained personnel. This work describes the development of a new, real-time PCR TaqMan assay for the detection of ling (Molva molva) in seafood products. For this purpose, specific primers and a minor groove binding (MGB) TaqMan probe were designed to amplify the 81 bp region on the cyt b gene. Efficiency, specificity and cross-reactivity assays showed statistically significant differences between the average Ct value obtained for Molva molva DNA (19.45 ± 0.65) and the average Ct for non-target species DNA (38.3 ± 2.8), even with closely related species such as Molva dypterygia (34.9 ± 0.09). The proposed methodology has been validated with 31 commercial samples The work was supported by the projects ‘‘GENTRASEA: Genetic Traceability of Fish Products. Rapid methods with DNA hybridiza- tion probes” funded by the Spanish Ministry of Science and Innova- tion AGL2009-13711-C03-01/ALI, and ‘‘LABELFISH: Atlantic Network on Genetic Control of Fish and Seafood Labelling and Traceability” (2011-1/163) funded by the Atlantic Area Program. The Spanish Ministry of Science and Innovation is gratefully acknowledged for the doctoral fellowship to L.T Peer reviewed